Adoption: adapting the school to the present moment (Journal of Parents and Teachers, 2012)
Schooling adopted children implies the need to understand the singular experiences that influence the child’s personality and learning styles. Every child has the right to grow up in a family and teachers have the chance to normalize the adoption as a legitimate way to create a family. In order to carry out this issue, the teacher can suggest several activities and avoid others, suggest the renovation of the books and the educative material and being tolerant with xenophobe incidents.
Keywords: Adoption; tolerance; family.